The Effects of Bimanual Coordination in Music Interventions on Executive Functions in Aging Adults - Bugos, Jennifer A. (Frontiers in Integrative Neuroscience, 2019)
Music training programs have been shown to enhance executive functions in aging adults; however, little is known regarding the extent to which different types of bimanual coordination (i.e., fine and gross motor) in music instruction contribute to these outcomes. The aim of this study was to examine the effects of bimanual coordination in music interventions on cognitive performance in healthy older adults (60-80 years). Participants (N=135) completed motor measures and battery of standardized cognitive measures, before and after a 16-week music training program with a three hour practice requirement. All participants were matched by age, education, and estimate of intelligence to one of three training programs: piano training (fine motor); percussion instruction (gross motor), and music listening instruction (no motor control condition). Results of a Repeated Measures ANOVA revealed significant enhancements in bimanual synchronization and visual scanning/working memory abilities for fine and gross motor training groups as compared to music listening instruction. Pairwise comparisons revealed that piano training significantly improved motor synchronization skills as compared to percussion instruction or music listening. Results suggest that active music performance may benefit working memory, the extent of these benefits may depend upon coordination demands.